2020
DOI: 10.1007/s10838-020-09502-w
|View full text |Cite
|
Sign up to set email alerts
|

Formal Models of Scientific Inquiry in a Social Context: An Introduction

Abstract: Formal models of scientific inquiry, aimed at capturing socio-epistemic aspects underlying the process of scientific research, have become an important method in formal social epistemology and philosophy of science. In this introduction to the special issue we provide a historical overview of the development of formal models of this kind and analyze their methodological contributions to discussions in philosophy of science. In particular, we show that their significance consists in different forms of 'methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…While it may turn out that such a threat is indeed relevant under specific conditions of inquiry, which exact conditions these are (when interpreted in terms of actual scientific practice) has remained largely underspecified in the literature. 20 From a more general point of view, our study provides support to recent calls for a modest treatment of results obtained by highly idealized agent-based models of scientific inquiry unless they have been empirically validated (Martini & Fernández Pinto, 2017;Frey & Šešelja, 2018;Thicke, 2020;Šešelja et al 2020;Šešelja, 2021; for a somewhat different viewpoint see Mayo-Wilson & Zollman, 2021).…”
Section: Searchsupporting
confidence: 59%
“…While it may turn out that such a threat is indeed relevant under specific conditions of inquiry, which exact conditions these are (when interpreted in terms of actual scientific practice) has remained largely underspecified in the literature. 20 From a more general point of view, our study provides support to recent calls for a modest treatment of results obtained by highly idealized agent-based models of scientific inquiry unless they have been empirically validated (Martini & Fernández Pinto, 2017;Frey & Šešelja, 2018;Thicke, 2020;Šešelja et al 2020;Šešelja, 2021; for a somewhat different viewpoint see Mayo-Wilson & Zollman, 2021).…”
Section: Searchsupporting
confidence: 59%
“…Philosophers have developed valuable simulation models for investigating group behavior in a variety of epistemic tasks (see Šešelja, Straußer, and Borg 2020). These models can be usefully modi ed to address issues of societal concern regarding the impact of demographic diversity.…”
Section: Empirically Sensitive Robustness In Simulation Studiesmentioning
confidence: 99%
“…3 As a result, it has been suggested that the vast majority of ABMs developed in philosophy of science are currently only exploratory, rather than explanatory (Frey and Šešelja 1. For a recent overview of formal models of scientific inquiry see Šešelja, Straßer, and Borg 2020. 2. Of special relevance here is the work by Kuhn, Lakatos, Feyerabend, Laudan, and others who advanced historicist theories of scientific rationality (Nickles 2017).…”
Section: Introductionmentioning
confidence: 99%